IMPORTANCE OF HUMANISTIC COUNSELLOR ATTITUDE OF EMPATHY AND ACCEPTANCE IN HELPING BURNOUT UNDERGRADUATE STUDENTS - Ghozali, Muhamad Afifuddin; Zulazmi, Mohd Aziz; A'yunin, Watik Qurrotu; Rahmah, Bintang Mutia; Habibah, Mayda Nurul; Nugroho, Tri Cahyo (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Burnout among university students is becoming an increasingly concerned issue, especially with consistently increasing academic pressures, social, and personal expectations, hindered them from being reaching stability in mental health. Humanistic Counselling, derived from Person-Centred Therapy with key aspects including acceptance and empathy, offers an effective and meaningful perspective in helping undergraduates overcoming episode of burnout. Acceptance allows students to feel valued and accepted for who they are, without judgment, while empathy gives them space to feel deep emotional understanding and support. This article aims to explore and examine humanistic counsellor’s attitude of acceptance and empathy and its part in the counselling session to hinder and help undergraduate students experiencing burnout. The method used is descriptive qualitative from two clients in several counselling session recorded in field note and interview. Through the counselling session using humanistic counselling, it is found that students had huge amount of opportunity in exploring their feelings, accepting their circumstances without shame, and getting support for long-term recovery while distancing from the burnout triggers. Moreover, acceptance and empathy shown in counsellor’s attitude accelerated the healing process and help students regain the emotional and mental stability post burnout in need to face increasing academic expectations both internally and externally alongside with routine challenges.